Evidence for a Common Origin of Homomorphic and Heteromorphic Sex Chromosomes in Distinct Spinacia Species. Issue 8 (1st August 2015) - Fujito, Satoshi; Takahata, Satoshi; Suzuki, Reimi; Hoshino, Yoichiro; Ohmido, Nobuko; Onodera, Yasuyuki
Abstract: The dioecious genus Spinacia is thought to include two wild relatives ( S . turkestanica Ilj. and S . tetrandra Stev.) of cultivated spinach ( S . oleracea L.). In this study, nuclear and chloroplast sequences from 21 accessions of Spinacia germplasm and six spinach cultivars or lines were subjected to phylogenetic analysis to define the relationships among the three species. Maximum-likelihood sequence analysis suggested that the Spinacia plant samples could be classified into two monophyletic groups (Group 1 and Group 2): Group 1 consisted of all accessions, cultivars, and lines of S . oleracea L. and S . turkestanica Ilj. and two of five S . tetrandra Stev. accessions, whereas Group 2 was composed of the three remaining S . tetrandra Stev. accessions. By using flow cytometry, we detected a distinct difference in nuclear genome size between the groups. Group 2 also was characterized by a sexual dimorphism in inflorescence structure, which was not observed in Group 1. Interspecific crosses between the groups produced hybrids with drastically reduced pollen fertility and showed that the male is the heterogametic sex (XY) in Group 2, as is the case in S . oleracea L. (Group 1). Cytogenetic and DNA marker analyses suggested that Group 1 and Group 2 have homomorphic and heteromorphic sex chromosome pairs (XY), respectively, and that the sex chromosome pairs of the two groups evolved from a common ancestral pair. Our data suggest that the Spinacia genus may serve as a good model for investigation of evolutionary mechanisms underlying the emergence of heteromorphic sex chromosome pairs from ancestral homomorphic pairs.